Family Harmony and Da'wah: Preventing Juvenile Delinquency Through Da'wah Program by the Paccinongan Youth Harmony Association - Ibnu Azka; Nurul Ramadhani; Fathur Baldan Haramain (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Adolescents are a group that is vulnerable to experiencing various complex problems in various aspects of their lives. This research aims to explore the factors that influence adolescent problems and identify effective coping strategies. A qualitative approach was used in this research, with data collection techniques in the form of observation, in-depth interviews, and document analysis. The research results show that adolescent problems cover various aspects, such as mental disorders, family conflicts, negative relationships, drug use, and the inability to manage emotions. Factors contributing to these problems include the social environment, individual factors, and media influence. In addition, this research shows that the da'wah program implemented by IKPP positively contributes to preventing juvenile delinquency through various activities such as lectures, religious studies, and skills training. Apart from that, this program also pays special attention to strengthening family harmony through education about the importance of good communication between family members, understanding religious values, and fostering the role of parents in educating children. This research reveals that integrating da'wah and strengthening family harmony is a practical approach to preventing juvenile delinquency. This research implies the crucial role of community organizations such as IKPP in positively contributing to efforts to prevent juvenile delinquency through a holistic and integrated approach.